2020
DOI: 10.12659/msm.922794
|View full text |Cite
|
Sign up to set email alerts
|

Root Anatomy and Root Canal Morphology of Maxillary Second Permanent Molars in a Chongqing Population: A Cone-Beam Computed Tomography Study

Abstract: Background To investigate variations in the anatomy of root canals in permanent second molars of the upper jaw in a population in Chongqing, China, using cone-beam computed tomography (CBCT). Material/Methods CBCT imaging data of 400 second permanent molars of the upper jaws of 200 patients were retrospectively reviewed. Patients’ gender, age, numbers of roots and canals, root fusion of permanent second molars of the maxilla on both sides, and morphological categories o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Endodontic therapy is more challenging for practitioners since root canal structural patterns differ by ethnicity [ [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. The effective management of periapical infections is crucial for the successful outcome of endodontic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Endodontic therapy is more challenging for practitioners since root canal structural patterns differ by ethnicity [ [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. The effective management of periapical infections is crucial for the successful outcome of endodontic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to use caution when comparing the position of the root with the image obtained from radiography. 19 Occasionally, it might be challenging to understand morphologic differences on a radiograph. Therefore, it is crucial to prioritise the use of an endodontic microscope, and use an electronic apex locator.…”
Section: Discussionmentioning
confidence: 99%
“…They discovered that the Asian ethnic group had a higher occurrence of Vertucci type I configuration in maxillay molars, while the white group exhibited a greater variety of morphologies in the multiple root canal system. Xia Y et al 19 (Table 1) analysed CBCT imaging data of 400 permanent molars in the upper jaws. They found that 78.0% of second molars had three roots, and fused roots were identified in 31.5% of the teeth.…”
Section: Search Methodologymentioning
confidence: 99%
“…Root and root canal morphology of different types of teeth has been analyzed in different populations, such as the Indian, Chinese, Korean, Israeli, Brazilian and Saudi Arabian populations, and the results obtained indicate that certain variations in root and root canal morphology are genetically determined [17][18][19][20][27][28][29]. Furthermore, these observations can be used for various epidemiological studies or the study of the ethnic origin of an individual.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite certain clues which might be present on orthopantomograms or periapical X-ray images, which are mainly used in daily clinical practice, radiographs are two-dimensional and it is often difficult to detect the presence of anatomical anomalies such as the "C"-shaped canal, radix entomolaris or paramolaris, or to determine the shape of multiple root canals and their possible merging into one canal. Therefore, cone-beam computed tomography (CBCT), which provides a three-dimensional analysis, is now widely used for diagnosis and in epidemiology as it is considered a suitable method to study the aforementioned anatomical variations in root canals, especially in epidemiologic studies [16][17][18][19]. It is a non-invasive method that allows the observation and analysis of teeth in all three planes, coronal, sagittal and transversal [20].…”
Section: Introductionmentioning
confidence: 99%